When People Parent Together: Let’s Talk About Coparenting - James McHale; Jason Baker; Heidi Liss Radunovich (EDIS)
FCS2277, a 7-page fact sheet by James McHale, Jason Baker, and Heidi Liss Radunovich, will help anyone who is "coparenting" children--raising children with the help of another adult. It explains why cooperative and respectful coparenting is key to the healthy development of children and will help coparents understand whether their coparenting relationship is in good health or in need of a tune-up. Published by the UF Department of Family, Youth and Community Sciences, October 2007.